# Why FCFF is not EBIT(1-t)+It

Hello,

The formula for FCFF is:

FCFF = [EBIT × (1 − tax rate)] + Dep − FCInv − WCInv

assuming the last 3 terms don’t apply (this will hold for the rest of the post)[1] we have:

FCFF = [EBIT × (1 − tax rate)] [2]

and I wonder why instead it’s not:

FCFF = [EBIT × (1 − tax rate)] + It

my rationale is; if we start with EBIT, once we subtract taxes we have the resulting cash left for debt and equity[1].

Alas:

FCFF = EBIT - T = EBIT - (EBIT - I)t = EBIT(1-t) - It

in the extreme case where t = 100%, FCFF = I, therefore with 100% tax rate the only cash available goes to pays interest, which to me makes sense with the definition of FCFF (cash available to equity and debtholders) and because any other resulting amount would go to pay taxes.

With the other formula [2] instead the FCFF in that case would be zero.

Thanks,

Pablo

EBIT (1 - t) is taking into consideration the tax shield from interest. You want to know cash available for boyh debt and equity holders.